1993
DOI: 10.1136/adc.69.4.440
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of respiratory syncytial virus infection with recombinant interferon alfa-2a.

Abstract: however, had a significantly higher overall score for severity of illness at the start of treatment. More rapid drop of the clinical score was observed in the INF-a-2a group after treatment in the first three days and the two groups had similar clinical severity by day 3. There was no significant difference of the duration ofviral shedding in the two groups. In conclusion, the overall clinical improvement was greater in the treatment group over the first three days, but the duration of viral shedding was not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 12 publications
0
23
1
Order By: Relevance
“…Unfortunately, the clinical trial showed that daily intramuscular injection of IFN-␣ into RSV-infected infants for three consecutive days did not change the overall clinical course, the duration of oxygen requirement, or viral shedding, although the treatment did induce a more rapid drop in the clinical score during the first 3 days (33). The difference between these human studies and our data in neonates may be explained by the different strategies that we employed.…”
Section: Discussioncontrasting
confidence: 54%
“…Unfortunately, the clinical trial showed that daily intramuscular injection of IFN-␣ into RSV-infected infants for three consecutive days did not change the overall clinical course, the duration of oxygen requirement, or viral shedding, although the treatment did induce a more rapid drop in the clinical score during the first 3 days (33). The difference between these human studies and our data in neonates may be explained by the different strategies that we employed.…”
Section: Discussioncontrasting
confidence: 54%
“…was added upon collection, were stored at Ϫ70°C and then shipped to the United States in the frozen state (Ϫ70°C). The culture methods for the detection of all viruses, including RSV, in clinical respiratory specimens were described previously (27). For detection of the viral antigen of RSV by IF, the cells from the clinical specimens were washed, concentrated, and spotted on slides.…”
Section: Methodsmentioning
confidence: 99%
“…For detection of the viral antigen of RSV by IF, the cells from the clinical specimens were washed, concentrated, and spotted on slides. The slides were then stained using IMAGEN (Dako Diagnostics, Ely, United Kingdom) and analyzed as described previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…One study reported that intramuscular treatment of RSV-infected children with IFN-␣ did improve their clinical course after the second day of treatment (53). On the other hand, Chipps et al reported that children with bronchiolitis caused by RSV who were treated with intramuscular injection of IFN-␣ did not show significant difference in the clinical course, duration of oxygen requirement, or physical assessment compared to a placebo group.…”
mentioning
confidence: 95%